2008
DOI: 10.1590/s1519-69842008000500016
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of the free-living freshwater Cyclopoida (Copepoda: Crustacea) in the Neotropics

Abstract: Cyclopoida species from the Neotropics are listed and their distributions are commented. The results showed 148 species in the Neotropics, where 83 species were recorded in the northern region (above upon Equator) and 110 species in the southern region (below the Equator). Species richness and endemism are related more to the number of specialists than to environmental complexity. New researcher should be made on to the Copepod taxonomy and the and new skills utilized to solve the main questions on the true di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 15 publications
2
20
0
6
Order By: Relevance
“…The other species cited only by Tundisi & Saijo (1997) and Moreto (2001) are considered synonyms, redescriptions or misidentifications as described hereafter. Mesocyclops brasilianus Kiefer, 1933 may be M. meridianus as both species are restricted to the southern hemisphere, despite the latter having a wider distribution (Silva 2008 (Segers & Smet 2008). The species Synchaeta stylata was cited by Moreto (2001) but in our study the individual was identified only until genus level.…”
Section: Resultsmentioning
confidence: 60%
“…The other species cited only by Tundisi & Saijo (1997) and Moreto (2001) are considered synonyms, redescriptions or misidentifications as described hereafter. Mesocyclops brasilianus Kiefer, 1933 may be M. meridianus as both species are restricted to the southern hemisphere, despite the latter having a wider distribution (Silva 2008 (Segers & Smet 2008). The species Synchaeta stylata was cited by Moreto (2001) but in our study the individual was identified only until genus level.…”
Section: Resultsmentioning
confidence: 60%
“…The Cyclopoida species registered in the reservoirs are part of the fauna of São Paulo State, according to Silva (2008). Silva and Matsumura-Tundisi (2005) also found the species Thermocyclops decipiens as being the most frequent in other reservoirs in São Paulo State.…”
Section: Copepodamentioning
confidence: 95%
“…As stated by Silva (2008), E. neumani titicacae was previously known to be restricted to its type locality, Lake Titicaca, where it has also been recorded as E. neumani (Ueno 1966). However, it was realized that an older record of "Cyclops serrulatus" published by Pearse (1922) from Lake Valencia, Venezuela, was assignable to E. neumani titicacae (Reid 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The freshwater cyclopoid copepod Eucyclops neumani (Pesta, 1927), described originally from Argentina, is known to contain two subspecies, E. neumani neumani (Pesta, 1927), distributed mainly in Argentina, Paraguay and Brazil (Reid 1985, Dussart & Frutos 1986, Silva 2008, Mercado-Salas et al 2012) and E. neumani titicacae Kiefer 1957, originally described from Lake Titicaca (Peru and Bolivia) (Kiefer 1957). According to Alekseev & Defaye (2011), E. neumani titicacae is a member of the E. serrulatus species group, comprising species with 12-segmented antennules bearing a smooth hyaline membrane on the three distal segments, caudal ramus of moderate length (3.5-7.0 length/width ratio), a strong inner spine of leg 5, and one or two groups of hairs on the distal margin of the antennary basipodite, among other characters.…”
Section: Introductionmentioning
confidence: 99%